A compositional technique of task solution of trade stock that loses natural properties - Єгорова, Ольга В’ячеславівна (Technology audit and production reserves, 2015)
The mathematical models of the problem of task of trade stock that lose their natural properties, taking into account complex factors, are given in the article. Parametric identification of the given models is complex, non-trivial process that requires the use of a method that does not depend on the choice of starting point and does not require verification of additional restrictions on the characteristics of the objective function. It is proposed a composite method of direct optimization adapted to the task solution of trade stock that loses natural properties, taking into account complex factors. The algorithm of its implementation in search space of possible solutions is investigated. The aspects of program implementation of the method are considered. The experimental verification of models is done. The experiments show that the best results are obtained within a reasonable time are obtained in the case of developed punitive function compared with adaptive and fuzzy punitive functions, due to their focus on simulation of fuzzy variables.